2022
DOI: 10.3390/economies10030068
|View full text |Cite
|
Sign up to set email alerts
|

Digitalisation in Hospitals in COVID-19 Times—A Case Study of the Czech Republic

Abstract: In COVID-19 times, the healthcare system needs more financial and other resources for covering all necessary medical products and services. On the other hand, we have observed pressure on the effectiveness and optimisation of resources in hospitals and healthcare facilities. Digitalisation represents an important source of information for various levels of management in hospitals. The main aim of our research is the identification of the benefits of digitalisation of medical devices in hospitals in COVID-19 ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The results produced in this work run parallel with previous research on the cost of digitisation. It [66] considers the cost of digitization as a barrier to its implementation; hence, the present research highlights this factor, emphasizing the role of the cost-benefit analysis to better understand the impact of digitization processes implemented in enterprises, which is also in line with statements in the literature [66,67].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The results produced in this work run parallel with previous research on the cost of digitisation. It [66] considers the cost of digitization as a barrier to its implementation; hence, the present research highlights this factor, emphasizing the role of the cost-benefit analysis to better understand the impact of digitization processes implemented in enterprises, which is also in line with statements in the literature [66,67].…”
Section: Discussionsupporting
confidence: 60%
“…Even though the literature mentions the perception of digitalisation as being expensive, some studies highlight the role of cost-benefit analysis to better understand the impact of digitalisation processes deployed within businesses [66,67]. An uncommon perspective places the digitalisation as a stimulus for corporate social responsibility.…”
Section: Strategies and The Costs Of Digitalisationmentioning
confidence: 99%
“…In [8], the feasibility of digitization was proposed in the aftermath of the COVID-19 pandemic, which meant an acceleration in the digital transformation, efficiently storing all physical medical records. In summary, the article discusses how the digitalization of hospitals has become increasingly important due to the need to minimize physical contact.…”
Section: Related Workmentioning
confidence: 99%
“…Zimmermannova et al [24] examined the benefits of the digitalization of medical devices during the COVID-19 pandemic through a thorough literature review, complemented with a regression and correlation analysis. The results indicated that the COVID-19 pandemic has significantly influenced resource distribution and hospital management, with digitalization being recommended as a tool for improving health systems.…”
Section: Literature Reviewmentioning
confidence: 99%